2020
DOI: 10.1177/0886260519898443
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors Associated With Intimate Partner Violence Among Women in Haiti: Understanding Household, Individual, Partner, and Relationship Characteristics

Abstract: Intimate partner violence (IPV) is a significant public health issue with detrimental consequences for women’s reproductive, mental, and physical health. In Haiti, IPV is a major obstacle to women’s development. Yet, the determinants of IPV victimization are still not well understood. In this study, we utilized the 2016–2017 Haiti Demographic and Health Survey to determine the prevalence of IPV victimization and its subtypes (emotional, physical, and sexual abuse) among married or cohabiting women ( N = 3,805)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 25 publications
3
10
0
Order By: Relevance
“…The study also found that women whose husbands use alcohol are at high risk of experiencing intimate partner violence, which is consistent with findings from other studies [ 18 , 23 , 34 , 35 , 41 , 42 ]. Other studies discovered that both men's and women's alcohol consumption was a risk factor for IPV [ 44 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The study also found that women whose husbands use alcohol are at high risk of experiencing intimate partner violence, which is consistent with findings from other studies [ 18 , 23 , 34 , 35 , 41 , 42 ]. Other studies discovered that both men's and women's alcohol consumption was a risk factor for IPV [ 44 ].…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence rate of IPV in the current study is high when compared to the study conducted just before the pandemic [ 32 ]. The increase in prevalence of IPV was also reported in other countries in similar recent studies, for example, 42% in Malawi [ 33 ], 40% in Gambia [ 34 ], and 32.5% in Haiti [ 35 ], and 42.7%in Zimbabwe [ 36 ].…”
Section: Discussionsupporting
confidence: 77%
“…This indicated the increase of IPV during the pandemic. High prevalence of IPV was also reported in some other countries in similar recent studies, for instance, 42% in Malawi ( Chikhungu et al., 2019 ), 56.7% in Southern India ( George et al., 2016 ), 40% in Gambia ( Jabbi et al., 2020 ), 42.7% in Zimbabwe ( Lasong et al., 2020 ), and 32.5% in Haiti ( Occean et al., 2020 ). A recent study of Hamadani et al.…”
Section: Discussionsupporting
confidence: 68%
“…Haiti had high levels of poverty and violence. In addition, social norms maintain gender imbalances, women's poverty, and acceptance of IPV, leading to reduced reporting of IPV [33,34]. For all these differences among countries, we conducted an overall latent class model and tested the multigroup latent class in which we found classes were similar between countries.…”
Section: Limitationsmentioning
confidence: 99%